2010
DOI: 10.1007/s00281-010-0205-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathology of the human pancreas in type-I diabetes

Abstract: Type 1 diabetes is a chronic autoimmune disease characterised by the selective destruction of pancreatic beta (β) cells. The understanding of the aetiology of this disease has increased dramatically in recent years by the study of tissue recovered from patients, from analysis of the responses of isolated islet and β-cells in tissue culture and via the use of animal models. However, knowledge of the immunopathology of type 1 diabetes in humans is still relatively deficient due largely to the difficulty of acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 90 publications
3
71
1
Order By: Relevance
“…IKK2-CA Pdx-1 animals develop severe hyperglycemia and hypoinsulinemia mirroring substantial b-cell loss that is associated with marked islet inflammation. Similar to the human immunopathology, infiltrates are not seen in all pancreatic islets and include different kinds of immune cells (21). This model is the first animal model to activate IKK2/NF-kB in b-cells and to prove directly its capability to trigger diabetes development on its own.…”
Section: Discussionmentioning
confidence: 99%
“…IKK2-CA Pdx-1 animals develop severe hyperglycemia and hypoinsulinemia mirroring substantial b-cell loss that is associated with marked islet inflammation. Similar to the human immunopathology, infiltrates are not seen in all pancreatic islets and include different kinds of immune cells (21). This model is the first animal model to activate IKK2/NF-kB in b-cells and to prove directly its capability to trigger diabetes development on its own.…”
Section: Discussionmentioning
confidence: 99%
“…Although immunohistochemical studies have suggested the expression of type I IFN (10,11) and some ISGs (12,13) in T1D islets, other studies have failed to detect type I IFN in pancreata from subjects with diabetes (14). End point PCR, with no or limited quantitative value, has suggested IFN-a expression to be more prevalent in T1D than in control pancreata (15,16), but this has not been confirmed by quantitative methods.…”
mentioning
confidence: 98%
“…Children genetically at risk for type 1 diabetes present a type I IFNinducible transcriptional signature that precedes the development of autoantibodies [14,15], and IFNα plays a major role as mediator of HLA class overexpression in human islet cells, a key event in early type 1 diabetes [16,17]. Laser-captured islets obtained from living donors with recent onset type 1 diabetes showed a significant increase in nearly 50% of the IFN-stimulated genes (ISGs) evaluated [18].…”
Section: Introductionmentioning
confidence: 99%